KEDUDUKAN LEMBAGA PERLINDUNGAN SAKSI DAN KORBAN TERHADAP PERLINDUNGAN HAK ANAK YANG BEKELANJUTAN DI INDONESIA (Lex Jurnalica, 2017)
AbstractThe Agency was born as an independent state agency that protects witnesses and victims (especially child protection). As an independent state institution in his way, the Agency also has the disadvantage that results in a reduction in the maximum in performing his duties as an Independent State institutions that protect witnesses and victims are children. This study is normative, which examined: 1) The position of the Agency as an independent state institution in Indonesia? 2) How is the Agency's role in protecting the rights of children as witnesses and victims in Indonesia? 3) How is the ideal concept in delivering sustainable child protection in Indonesia. Position Independent Agency is a state institution in Indonesia has been apparent in accordance with Law No. 13 of 2006 on Protection of Witnesses and Victims. In carrying out its role in the protection of children in Indonesia, the Agency is also working with other state agencies that support child protection activities, as well as NGOs and communities in realizing child protection. Sustainable child protection is a good idea in implementing child protection in Indonesia, with the concept of sustainable will take continuous action on an ongoing basis and there is no stopping point. Keywords: Child, suistanable, rights, LPSK, protection. AbstrakLPSK lahir sebagai sebuah lembaga negara independen yang melindungi saksi dan korban (terutama dalam perlindungan anak). Sebagai lembaga negara independen di dalam perjalanannya, LPSK juga memiliki kelemahan yang mengakibatkan kurang maksimalnya di dalam menjalankan tugasnya sebagai Lembaga Negara Independen yang melindungi saksi dan korban yaitu anak. Penelitian ini merupakan penelitian yuridis noramatif, yang meniliti: 1) Bagaimana kedudukan LPSK sebagai lembaga negara independen di Indonesia? 2) Bagaimana peran LPSK di dalam melindungi hak-hak anak sebagai saksi dan korban di Indonesia? 3) Bagaimana konsep ideal di dalam mewujudkan perlindungan anak yang berkelanjutan di Indonesia. Kedudukan LPSK sebagai lembaga negara Independen di Indonesia sudah jelas sesuai dengan Undang-Undang Nomor 13 tahun 2006 Tentang Perlindungan Saksi Dan Korban. Didalam menjalankan perannya didalam perlindungan anak di Indonesia, LPSK juga bekerjasama dengan lembaga-lembaga negara lainnya yang mendukung kegiatan perlindungan anak, serta Lembaga Swadaya Masyarakat dan Masyarakat dalam mewujudkan perlindungan anak. Perlindungan anak yang berkelanjutan merupakan gagasan yang baik di dalam melaksanakan perlindungan anak Indonesia, dengan konsep berkelanjutan akan membawa tindakan yang terus menerus secara berkesinambungan dan tidak ada titik hentinya. Kata kunci: Anak, berkelanjutan, hak, LPSK, perlindungan.